A incidência de Leishmaniose visceral humana na cidade de Araguaína e sua relação com indicaores socioambientais locais. - Sousa, Roberto Neves de (Universidade Federal do Tocantins, 2023)
Studies have shown that the municipality of Araguaína has for many years concentrated the highest rates of Canine Visceral Leishmaniasis (LVC) and Human Visceral Leishmaniasis (LVH) in the state of Tocantins, influenced, among others, by socio-environmental factors. Faced with this reality, this research was carried out, which had the general objective of analyzing VHL data in the city of Araguaína and discussing its relationship with local socio-environmental indicators of basic sanitation as a contributor to the incidence of this disease. In search of answers to the question-problem, that is, if the local socio-environmental indicators interfere in the incidence data of LVH in the city of Araguaína, a descriptive-explanatory study was developed, with a quantitative and qualitative approach and using documental research as a technical data collection procedure. Information on the evolution of the water and sewage system, in the 2010-2020 period, was obtained through the National Sanitation Information System. Finally, data on the prevalence of CVL and incidence of VHL, in the period, were provided by the Center for Control of Zoonoses (CCZ), and Litucera – Cleaning and Engineering provided a garbage collection service schedule. The results allow us to conclude that access to treated water and exclusive use of a bathroom has contributed to the decline in the incidence of VHL, but not to the reduction in the rates of LVC, which can be attributed to the number of households without access to the sanitation service. sewage collection and the number of unrestricted dogs and vacant lots.